Role of miR-182 in cardiovascular and cerebrovascular diseases - Pei, Gaiqin; Chen, Li; Wang, Yang; He, Chengqi; Fu, Chenying; Wei, Quan (Frontiers in Cell and Developmental Biology, 2023)
The treatment of cardiovascular and cerebrovascular diseases have undergone major advances in recent decades, allowing for a more effective prevention of cardiovascular and cerebrovascular events. However, cardiac and cerebral atherothrombotic complications still account for substantial morbidity and mortality worldwide. Novel therapeutic strategies are critical to improve patient outcomes following cardiovascular diseases. miRNAs are small non-coding RNAs, that regulate gene expression. Here, we discuss the role of miR-182 in regulating myocardial proliferation, migration, hypoxia, ischemia, apoptosis and hypertrophy in atherosclerosis, CAD, MI, I/R injury, organ transplant, cardiac hypertrophy, hypertension, heart failure, congenital heart disease and cardiotoxicity. Besides, we also summarize the current progress of miR-182 therapeutics in clinical development and discuss challenges that will need to be overcome to enter the clinic for patients with cardiac disease.